SINKRONISASI KEBIJAKAN DI BIDANG IZIN PERTAMBANGAN DALAM KAWASAN HUTAN - Epi Syahadat; Subarudi Subarudi; Andri Setiadi Kurniawan (Jurnal Analisis Kebijakan Kehutanan, 2018)
The management of licensing system, especially mining permits, is complex because of the inter-sectoral legal linkages. Legislation has been regulated in such a way that certained procedures must be passed by permit applicants to obtain izin pinjam pakai kawasan hutan (IPPKH) and izin usaha pertambangan (IUP). But there is always a gap between regulations and their implementation which makes the licensing system more complex. The aims of the research are (a) to identify mining licensing policies in forest area, (b) to synchronize mining licensing system, and (c) to improve mining licensing system. This study used a content analysis method with a retrospective process evaluation approach. The results showed that IPPKH policy involves 36 types of regulations consisting of 11 Acts, 13 Government Regulations, nine Presidential Regulations, and three Environment and Forestry Ministerial Regulations. The IPPKH process is considered less effective because the applicants must get IUP from the Ministry of ESDM and IPPKH from the Ministry of  Environment and Forestry which is managed under One Stop Integrating Permits system, which only handles the administrative issues as mandated by President Regulation No 97/2014. The synchronization of IPPKH policy is necessary to accommodate legislation issued by other technical ministries.